A clash of internationalizations: New Zealand and the Bologna Process. Issue 1 (2nd January 2019) - Shannon, William; Doidge, Mathew; Holland, Martin
ABSTRACT: In this paper we examine the normative and strategic impact of the Bologna Process on the New Zealand University system. We argue that, from a normative perspective, Bologna has not resulted in substantive change. Nevertheless, a specific, if low-level, normative response has been evident, driven by perceived market incentives and the market-based norms that underpin higher education and internationalization strategies in the New Zealand context. We contend that this response necessitates a conceptual extension of the normative power framework. From a strategic perspective, we consider the extent to which Bologna has succeeded in making Europe a geographic focus in New Zealand University internationalization strategies. In this respect, we find strategic priorities lie elsewhere, again reflecting the competitive market-based norms that underpin higher education in New Zealand.